Implementasi Metode Diskusi dan Resitasi dalam Meningkatkan Prestasi Belajar Mata Pelajaran PKn Siswa Kelas V SDN Ambat - Selamet Riyadi (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2015)
This research is aimed to know (1) How is the implementation of Discussion and Recitation methodin improving students’ activeness in learning PKn? and (2) is the application of Discussion and Recitationmethod able to improve students’ achievement in learning PKn?. This research uses Classroom ActionResearch. Data of the research are collected by using observation and field note and are analysed through datareduction, inference, follow up, and conclusion drawing. The result of the research shows that Discussion andRecitation method is able to improve students’ activeness in learning PKn. The students’ activeness in learningPKn is stimulated through giving appreciation as well as giving additional scores to active students during thediscussion proses. this condition is proved by the fluency of the students in learning, writing, memorizing PKnlearning materials being discussed in settled groups. Thus, it can be concluded that application of Discussionand Recitation method can improve students’ activeness and students’ achievement in learning PKn in SDNAmbat Kecamatan Janapria Kabupaten Lombok Tengah in academic year 2015/2016. Therefore, it issuggested that teachers implement Discussion and Recitation method in teaching PKn towards studentselementary